MENGENAL ASESMEN KOMPETENSI MINIMUM (AKM): PELATIHAN GURU YAYASAN PONDOK PESANTREN FATHUL HIDAYAH LAMONGAN - Purwasih, Joan Hesti Gita; Wahananto, Juri (Universitas Negeri Malang, 2022)
(KNOWING THE MINIMUM COMPETENCY ASSESSMENT: TEACHER TRAINING OF THE FATHUL HIDAYAH BOARDING SCHOOL LAMONGAN FOUNDATION) The Minimum Competency Assessment (AKM) is a new policy in the world of education that has not been fully reached by teachers. The AKM questions are centered on measuring literacy and numeracy mastery. Strengthening literacy and numeracy does not only rely on Indonesian and Mathematics subjects. Other subjects also need to provide strengthening of these competencies. Therefore, teachers need to understand concepts, rules, and practices in developing literacy and numeracy-based questions. Experimental research with the type of one group pretest-posttest design was carried out through pretest, socialization, practice, and posttest techniques. As a result, improving the competence of teachers was able to provide optimal results. The results of the pretest showed a value of 48 and increased to 72 on the post. Thus, the results of this experiment can increase considerations for providing strengthening training to teachers in schools. Asesmen Kompetensi Minimum (AKM) merupakan kebijakan baru dalam dunia pendidikan yang belum sepenuhnya dipahami oleh guru. Soal AKM berpusat pada pengukuran penguasaan literasi dan numerasi. Penguatan literasi dan numerasi tidak hanya bertumpu pada mata pelajaran Bahasa Indonesia dan Matematika. Mata pelajaran lain juga perlu memberikan penguatan kompetensi tersebut. Oleh karena itu, guru perlu memahami konsep, kaidah, hingga praktik dalam pengembangan soal-soal berbasis literasi dan numerasi. Penelitian eksperimen dengan jenis one group pretest-posttest design dilakukan melalui teknik pretes, sosialisasi, praktik, hingga postes. Hasilnya, penguatan kompetensi guru ternyata mampu memberikan hasil yang optimal. Hasil pretes menunjukkan nilai 48 dan meningkat menjadi 72 pada postes. Dengan demikian, hasil eksperimen ini dapat memberikan penguatan pertimbangan untuk memberikan penguatan pelatihan kepada guru di sekolah.